2019
DOI: 10.3390/plants8030056
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitrate Reductase in NO Production in Photosynthetic Eukaryotes

Abstract: Nitric oxide is a gaseous secondary messenger that is critical for proper cell signaling and plant survival when exposed to stress. Nitric oxide (NO) synthesis in plants, under standard phototrophic oxygenic conditions, has long been a very controversial issue. A few algal strains contain NO synthase (NOS), which appears to be absent in all other algae and land plants. The experimental data have led to the hypothesis that molybdoenzyme nitrate reductase (NR) is the main enzyme responsible for NO production in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 110 publications
2
31
0
3
Order By: Relevance
“…() have shown that NO accumulation was present in the root‐knot nematode Meloidogyne incognita infected‐tomato roots at early stages of infection. However, the NO issue remains unexplained during plant infection with cyst nematodes, and this is important because NO synthesis in plants is coordinated with N metabolism (Tejada‐Jimenez et al , ). Our research team are therefore working on this issue, and our experiments have shown that the role of NO metabolism during plant–CN interactions is significant (authors' unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…() have shown that NO accumulation was present in the root‐knot nematode Meloidogyne incognita infected‐tomato roots at early stages of infection. However, the NO issue remains unexplained during plant infection with cyst nematodes, and this is important because NO synthesis in plants is coordinated with N metabolism (Tejada‐Jimenez et al , ). Our research team are therefore working on this issue, and our experiments have shown that the role of NO metabolism during plant–CN interactions is significant (authors' unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine whether N 2 O production can be evidenced in the absence of exogenous NO supply, algae were supplied with nitrite as a nitrogen source, nitrite reduction being documented as an important source of intracellular NO (28). Note that we did not use nitrate here since the C. reinhardtii mutant strains used in this study all lack the nitrate reductase (27).…”
Section: Light-dependent N 2 O Photoproduction Mostly Relies On Flvsmentioning
confidence: 99%
“…Nevertheless, the NO 2 accumulation, by NO 3 supplied, occurred with and without NH 4 . Furthermore, NO 2 is a product of nitrate reduction within the N assimilation pathway and its concentrations in the cytosol are maintained at a micromolar range to prevent NO 2 toxicity in the cell [42,43]. This ion in addition to being channelled through the ammonium assimilation pathway is capable of being reduced in nitric oxide, which is a by-product of hypoxic N metabolism in the root.…”
Section: Resultsmentioning
confidence: 99%